“How Dare You!”—The Influence of Fridays for Future on the Political Attitudes of Young Adults - Parth, Anne-Marie; Weiss, Julia; Firat, Rojda; Eberhardt, Manuel (Frontiers in Political Science, 2020)
In recent years, young adults have increasingly expressed their displeasure with climate policies, arguing that the preservation of the earth for future generations is not secured by existing policies. A growing number of young citizens demands action from politicians and accuses them of a lack of responsiveness. At the same time, young adults are undergoing political socialization, not only within their families, but especially in school, where they learn to lead an independent life and to form their own political opinions. However, what happens if students question the knowledge on the political system that they have acquired in school? This paper analyses how the exogenous “shock” of Fridays for Future has influenced pupils' political attitudes compared to other continuous skills that pupils learn in school. Relying on a unique survey experiment among pupils from different school types and among students in Germany (more than 300 respondents), we find that priming for Fridays for Future and protest participation significantly change perceived political responsiveness and satisfaction with democracy. The results demonstrate that the efforts of schools to prepare young citizens for professional life have no effect, while equal treatment in school is explanatory for varying political satisfaction. Protest participation seems to have a great influence on how the political attitudes of the young cohort develop.